Biography of British writer C.S. Lewis - Farmanov Gayrat (Лучшие интеллектуальные исследования, 2024)
Abstract: C.S. Lewis (November 29, 1898 – November 22,1963) was a British fantasy writer and scholar. Known for his imaginative fantasy world of Narnia and, later, his writings on Christianity, Lewis’ life was informed by a search for higher meaning. He remains to this day one of most beloved children’s authors in English.